2016
DOI: 10.1038/srep35638
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stem/Progenitor Cells Attenuate the Inflammatory Milieu Following Substitution Urethroplasty

Abstract: Substitution urethroplasty for the treatment of male stricture disease is often accompanied by subsequent tissue fibrosis and secondary stricture formation. Patients with pre-existing morbidities are often at increased risk of urethral stricture recurrence brought upon in-part by delayed vascularization accompanied by overactive inflammatory responses following surgery. Within the context of this study, we demonstrate the functional utility of a cell/scaffold composite graft comprised of human bone marrow-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…In a more nuanced role, HSPCs can enhance or diminish the highly educated adaptive immune system through MDSC‐like immune suppression or myeloid antigen‐presenting cell‐like immune activation . In each of these functions, HSPCs can enable or prevent infections, autoimmunity, cancers, and even modulate surgical site healing responses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more nuanced role, HSPCs can enhance or diminish the highly educated adaptive immune system through MDSC‐like immune suppression or myeloid antigen‐presenting cell‐like immune activation . In each of these functions, HSPCs can enable or prevent infections, autoimmunity, cancers, and even modulate surgical site healing responses .…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic stem and progenitor cells (HSPCs) at various stages of multipotency and lineagecommitment have been implicated as key modulators of immunity [1]. Namely, it has been suggested that HSPCs can regulate cancer progression [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], drive autoimmunity [18][19][20], and regulate infections and inflammation [1,[20][21][22][23][24][25][26][27][28][29][30]. In each of these disease settings, multiple reports have described HSPC-mediated immune-suppressive and stimulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that bone marrowderived mesenchymal stem cells in combination with CD34 ? hematopoietic stem/progenitor cells can offer inflammatory modulation, increase vascularization and improve wound healing by reduction of collagen III:I production [23]. However, adipose derived stem cells (ASCs), seem be superior over other cell sources [1].…”
Section: Stem Cellsmentioning
confidence: 99%
“…Recently various strategies, including growth factors administration, gene therapy, and stem cell transplantation, have been used to improve the treatment of urethral stricture . Among these, the transplantation of mesenchymal stem cells (MSC)—the multipotent stromal progenitor cells—has been proved to enhance the tissue repair process and resulted in better performance . Large number of papers indicated that both multi‐potential ability to differentiate into specialized cells for injury replacement and its paracrine effects to regulate the wound healing process, contribute to high therapeutic potential of MSCs during tissue repair or regeneration process .…”
Section: Introductionmentioning
confidence: 99%
“…4,[7][8][9] Among these, the transplantation of mesenchymal stem cells (MSC)-the multipotent stromal progenitor cells-has been proved to enhance the tissue repair process and resulted in better performance. 10,11 Large number of papers indicated that both multi-potential ability to differentiate into specialized cells for injury replacement and its paracrine effects to regulate the wound healing process, contribute to high therapeutic potential of MSCs during tissue repair or regeneration process. [7][8][9] However, because of the unfavourable microenvironment in the repair site, such as inflammation and over-production of ROS induced oxidative stress, the poor viability of MSC at the transplanted site might significantly decreased its therapeutic potential performance.…”
mentioning
confidence: 99%